Relationship between Knowledge and Attitude with Treatment Delay in Stadium IV Colorectal Cancer Patients - Zaki Yamani; Aries Budianto; Solimun Solimun (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Colorectal cancer is the fourth most common cancer in the world. Stage IV colorectal cancer are often late for treatment and have poor prognosis. Knowledge and attitude factors are known to play a role in treatment delay. Therefore, this study aims to determine the relationship between knowledge and attitudes on treatment delay of stage IV colorectal cancer patients at Saiful Anwar Hospital, Malang (RSSA). Material and Methods: The research design was a cause-effect retrospective study conducted at RSSA from June 2021 to December 2021. Measurement of patient knowledge and attitudes using questionnaires while patient delays in seeking treatment are obtained from medical records. Statistical analysis using structural equation modelling (SEM) using the WarpPLS application with a significance level of p<0.05. Results: The result of this research indicated that the knowledge of symptoms is associated with the patient's anxiety attitude (p<0.01; r=-0.31) and attitude to screening (p=0.03; r=0.21). Knowledge of a healthy lifestyle was associated with attitudes to screening (p<0.01; r=0.27). Screening attitude was associated with treatment delay in colorectal cancer patients (p<0.01; r=-0.42). Conclusion: The conclusion is the knowledge and attitudes of patients about colorectal cancer are associated with the treatment delay. Increasing knowledge and attitudes of patients can reduce the treatment delay on stage IV colorectal cancer patients to come to RSSA.